Therapeutic outcomes of customized 3D-printed ankle-foot orthoses in children with spastic cerebral palsy: a case series study - Qin, Cong; Luo, Xiang; Yang, Yan; Lun, Yongrong; Yang, Shali; Chen, Lingfeng (Frontiers in Pediatrics, 2025)
ObjectiveTo retrospectively evaluate the therapeutic effects of 3D-printed ankle-foot orthoses in children with spastic cerebral palsy (SPC).MethodsWe conducted a retrospective cohort study at Guigang People's Hospital, reviewing medical records of children diagnosed with SPC between January 2022 and June 2024. A total of 124 patients who met the inclusion criteria were divided into two groups based on the orthotic device they received: the treatment group (n = 62) used 3D-printed orthoses (aluminum alloy uppers with TPU soles), while the control group (n = 62) used traditional polyethylene orthoses. All patients underwent standardized rehabilitation training. Clinical outcomes including passive ankle dorsiflexion, Gross Motor Function Measure (GMFM) scores, and gait parameters (step length, width, and cadence) were assessed based on follow-up records at 3 months after orthotic use.ResultsBaseline data showed no significant differences between the two groups (P > 0.05). At the 3-months follow-up, both groups demonstrated functional improvements, with the treatment group exhibiting significantly greater gains. The passive ankle dorsiflexion angle in the treatment group was significantly lower (88.07 ± 3.18 degrees) than the control group (90.08 ± 2.65 degrees, P = 0.027). Post-treatment GMFM scores were significantly higher in the treatment group (74.98 ± 3.42 points) compared to the control group (69.08 ± 2.95 points, P = 0.001). The treatment group also showed significantly greater improvements in step length (increasing to 31.15 ± 4.18 vs. 28.68 ± 4.32 cm in control, P = 0.01), step speed (increasing to 0.56 ± 010 vs. 0.52 ± 0.12 m/s in control, P = 0.022), and reduced step width (decreasing to 14.52 ± 2.36 vs. 15.82 ± 2.40 cm in control, P = 0.011). The 3D-printed AFOs were significantly lighter (123.6 ± 36.15 g) and thinner (1.71 ± 0.17 mm) than the traditional AFOs (183.2 ± 65.78 g and 3.00 mm, P < 0.001).ConclusionThis retrospective study suggests that 3D-printed ankle-foot orthoses may offer improved comfort, durability, and functional benefits in gait performance among children with SPC compared to conventional orthoses.